Religious war and religious peace in early modern Europe - Te Brake, Wayne P. (Cambridge studies in contentious politics, 2017)
"Religious War and Religious Peace in Early Modern Europe presents a novel account of the origins of religious pluralism in Europe. Combining comparative historical analysis with contentious political analysis, it surveys six clusters of increasingly destructive religious wars between 1529 and 1651, analyzes the diverse settlements that brought these wars to an end, and describes the complex religious peace that emerged from two centuries of experimentation in accommodating religious differences. Rejecting the older authoritarian interpretations of the age of religious wars, the author uses traditional documentary sources as well as photographic evidence to show how a broad range of Europeans--from authoritative elites to a colorful array of religious 'dissenters'--replaced the cultural 'unity and purity' of late-medieval Christendom with a variable and durable pattern of religious diversity, deeply embedded in political, legal, and cultural institutions"--Provided by publisher